Kinovea analysis of high-speed video recording to determine kinematics of double pendulum in the long time scale - Wojewoda, Jerzy (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Measurement of position and velocity of rotating objects relies on installation of additional devices, which can significantly change their dynamic properties. Non-contact methods appear not to have the above-mentioned drawback. To determine the angular kinematics, a video measurement technique stands as a non-contact alternative. The rotational motion can be recorded with a high-speed camera and then analyzed with free and open-source tracking software which allows one to detect and digitize positions of chosen markers and then to calculate angular positions of selected elements. Differentiation process determines rotary speed values. Analysis of long-term dynamical behavior by recording data visualized as position maps which possess half of the information usually stored in the well-known Poincaré maps is proposed.